2019
DOI: 10.3390/ijms20092281
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide: A Multifaceted Paracrine Regulator in the Heart and Vasculature

Abstract: C-type natriuretic peptide (CNP) is an autocrine and paracrine mediator released by endothelial cells, cardiomyocytes and fibroblasts that regulates vital physiological functions in the cardiovascular system. These roles are conveyed via two cognate receptors, natriuretic peptide receptor B (NPR-B) and natriuretic peptide receptor C (NPR-C), which activate different signalling pathways that mediate complementary yet distinct cellular responses. Traditionally, CNP has been deemed the endothelial component of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 183 publications
3
73
0
1
Order By: Relevance
“…Thus, part of the cardioprotective effect of BNP in infarcted hearts is probably due to accelerated and/or increased neovascularisation in both the ZI+BZ and RZ. This result corroborates works reporting that natriuretic peptides stimulate angiogenesis and vasculogenesis during development and in adult ischemic organs 33,34 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, part of the cardioprotective effect of BNP in infarcted hearts is probably due to accelerated and/or increased neovascularisation in both the ZI+BZ and RZ. This result corroborates works reporting that natriuretic peptides stimulate angiogenesis and vasculogenesis during development and in adult ischemic organs 33,34 .…”
Section: Discussionsupporting
confidence: 93%
“…In addition CNP, via GC-B and possibly also NPR-C signaling, acts on other types of cells in the heart, such as fibroblasts, immune cells, and vascular cells (12,13,(18)(19)(20)(21)34). Thereby CNP may not only moderate cardiomyocyte stiffness and dysfunction (present studies) but also improve coronary perfusion and attenuate the hypertrophic, fibrotic, and inflammatory responses of the heart to ischemia and hypertension (12,13,42).…”
Section: Discussionmentioning
confidence: 59%
“…Various studies have demonstrated that NPR-C can inhibit the AC/cAMP signal transduction and elicit physiological functions [22]. Natriuretic peptides such as ANP, CNP and BNP have been reported to inhibit AC and decrease cAMP levels in a variety of tissues and cells by interacting with NPR-C receptor [22,23]. In addition, activation of NPR-C signaling may decrease L-type calcium current in single sinuatrial node cells by AC inhibition and decreased cAMP levels [24].…”
Section: Normal Npr-c Signalingmentioning
confidence: 99%